A study of learner styles and navigation strategies in hypertext. - Tan, Joyce Ai Lin. (2008)
An experimental study to determine the relationship between productivity with learner styles and navigation strategies. This experiment will facilitate companies as to which type of navigation stratgies to execute when publicizing their organization through the web.